Innovation in Physical Education to Raise Health Awareness in Elementary Schools - Sumarsono, Adi; Wasa, Carolus; Lewar, Emanuel; Yambedoan, Thadius (JUMORA: Jurnal Moderasi Olahraga, 2026)
This study uses a quantitative approach with SmartPLS 4 software to analyze the impact of Physical Education Learning Innovation on the physical activity of elementary school students located in the Indonesia-Papua New Guinea border region. In South Papua Province, Merauke, the results of the analysis using SmartPLS 4 software show that only certain indicators meet the test result requirements. Path coefficient test results, coefficient of 0.106, a t-value of 1.707, and a p-value of 0.088 (p > 0.05), so this hypothesis is rejected. However, only health awareness significantly influenced student activity, while physical education learning innovation did not. These findings highlight the crucial role of health awareness in encouraging physical activity among students.